(3eQbGI GdCfXGQ GdefJRY ef ZGjGJ GdCacGQ GdcGTa deYGfi ebOeI GdHMQ GdRNGQ GdeWhjI Ydi JhMjO PGJ GdhGMOs - (3YHO Gddg Hf eMeO Hf CHj GdbGSe GdfMQj,J (B877 (3g` s ((3CMeO SYjO GdQhjfi GdCSi s)
(3ChdgG (B:s
(3cJGH GdJhMjO GdcJGH ai GdCUd eUOQ , hGdeQGO Hg GdecJhH cGddaX HeYfi GdedahX s
(3BNQgG (B:s
(3aef QCi ebjekG ai OGQ GdaSb de jLH GdEfcGQ Ydjg EdG EPG Yde Cf ePgH Ch ePgH EeGeg hLhH GdgLQI , EdG GdEeGe adg Cf jfcQ Ydjg hjdReg ePgHg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM hHYV GdcdeGJ HGdeSjcs
(3Ydi WQJgG eWGdYGJ eDQNI SfI (B1141(3g` , (B1142 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B127s
Keywords: (3GdJhMjO hGdedd hGdfMds